Deskripsi Tingkat Pemahaman Konsep Perpangkatan Siswa Kelas XI Menggunakan Certainty of Response Index (CRI) - Hamzah Upu; Ahmad Talib; St. Hartina Tahir (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2020)
This study aims to determine the students understanding concept in terms of understanding the concept as well, understanding the concept but not sure, misconception, and not knowing the concept of exponent using Certainty of Response Index (CRI). The type of this study is qualitative study with descriptive approach. The subject of this study is 11 subjects who represent each level of conceptual understanding from class XI of Senior High School. The instruments of this study consist of objective test and interview guidelines. Level of conceptual understanding categorized using CRI category. The result of this study showed that: (1) The students understand with the concept as well because of their high motivation in learning and their love with mathematics. (2) The students understand with the concept but not sure because of their lack in self-confidence, their high false fear, lack in mastering the mathematic concept, and do not careful in answering the questions. (3) The Students experiencing misconceptions that caused by a lack of understanding, and even a misunderstanding towards the concept. (4) The students do not understand/ do not know the concept caused by their haven’t knowledge in answer the question of eksponent, their lack of ability and insight in working on the questions, lack of mastering the concept, not understanding the questions, and the students lack ability in transform the questions.